High‐Energy Nickel‐Cobalt‐Aluminium Oxide (NCA) Cells on Idle: Anode‐ versus Cathode‐Driven Side Reactions. Issue 6 (13th May 2021) - Zülke, Alana; Li, Yi; Keil, Peter; Burrell, Robert; Belaisch, Sacha; Nagarathinam, Mangayarkarasi; Mercer, Michael P.; Hoster, Harry E.
Abstract: Invited for this month's cover picture is the group of Prof. Harry Hoster at Lancaster University. The cover picture illustrates how state of charge (SoC) influences the capacity fade of a widely employed automotive Li‐ion battery chemistry when idle, e.g. when EVs are parked. The chemical degradation is revealed to be aggravated when devices are kept at around 80 % SoC. Read the full text of the Article at 10.1002/batt.202100046 . Abstract : "Idle power : NCA/Gr‐SiO x 21700 cells develop a spoon‐shaped profile of capacity fade as a function of state of charge (SoC) when idle. Cells at 100 % SoC have better capacity retention than cells stored at 80 or 90 % SoC but develop micro‐short circuits when exposed to temperatures over 40 °C. Our analysis supports the proposition of a cathode‐driven shuttle mechanism that alleviates loss of lithium to the (re)formation of the solid–electrolyte interphase (SEI). Those are interesting observations given that this type of commercial battery is widely employed in electric cars, in which SoCs are generally kept at high levels by their users…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article on 10.1002/batt.202100046 .